Association of Myosin Light Chain 2 (MLC 2) with Troponin-I and Ejection Fraction in patients with Acute Coronary Syndrome (Bangladesh Critical Care Journal, 2017)
Background: Acute coronary syndrome (ACS) is a major health problem and represents a large number of hospitalizations annually. Myosin light chain (MLC2)isasensitive early marker (within four hours) of ACS that can be used to confirm or exclude a diagnosis of acute cardiac condition. The present study was undertaken for rapid diagnosis ACS with the help of elevated MLC-2and its relation with Troponin I and ventricular ejection fraction.Method: In this cross sectional study,60 patients ofACS were enrolled from coronary care unit (CCU), BIRDEM as case and 25 apparently healthy people from cardiac point of view as control. Selection of patients was done according to the inclusion and exclusion criteria.MLC-2was measured(within 3-4 hours by ELISA method and level of ventricular dysfunction and troponin I (in ACS group) was taken from hospital records.Results: The mean ± SEM of MLC-2 was higher in the ACS group (88.02±18.0 pgm/ml) compared to the healthy control group (41.4±2.2 pgm/ml) and difference was statistically significant (p